Ethical Leadership and Innovative Work Behavior: The Mediating-Moderating Role of Psycho-Social Well-Being and Perceived Organizational Support - Ali Jufri; Muafi Muafi; Sari Laelatul Qodriah; Nuradli Ridzwan Shah Bin Mohd Dali (Journal of Management and Entrepreneurship Research, 2025)
Objective: This research aims to analyze how ethical leadership can encourage innovative work behavior among university lecturers, by also considering the mediating role of psycho-social well-being and the moderating role of perceived organizational support. Research Design & Methods: This study uses a quantitative approach through structural equation modeling (SEM) techniques using partial least squares (SmartPLS 3). Data were collected using a structured questionnaire sent to 332 university lecturers in West Java and Banten. Findings: Ethical leadership (EL) has a positive and significant influence on the innovative work behavior (IWB) of lecturers, both directly and through the mediation of psycho-social well-being (PSWB). Perceived Organizational Support (POS) has been proven to strengthen this relationship by enhancing the sense of belonging and affective commitment of lecturers towards the institution. Implications & Recommendations: For higher education institution administrators, the results of this study provide an empirical foundation for designing leadership policies and organizational interventions aimed at enhancing the psycho-social well-being and innovative capacity of lecturers. Contribution & Value Added: This research adds to the existing knowledge about leadership and innovative behavior by explaining how PSWB and POS help improve the effects of EL, particularly during times of digital change and the use of AI in higher education.